袋式包装机横封切杆机构的设计与特性分析 - 郭志强; 朱茹敏; 李冬龙 (Jixie chuandong)
The seals and crosscut mechanism is a basic and important actuating mechanism of bag packaging machine, usually its structure is designed to bar mechanism on experience and imitation. But the dynamic process of the seals and crosscut mechanism cannot truly be reflected and generates the large shock and vibration. So a quantitative analysis of kinetic and dynamic characteristics is taken by using the simulation method, it shows that the rigid impact is avoided and flexible impact is weaken to design the mechanism parameter.